ESTABLISHING VALIDITY AND RELIABILITY: A QUALITATIVE STUDY OF STUDENTS’ DROPOUT FACTORS IN SOKOTO METROPOLIS NIGERIA - INUWA, AWWALU MUHAMMAD (Sokoto Educational Review, 2025)
This study explores the factors contributing to student dropout in Sokoto metropolis, Nigeria. It investigates the influence of parental factors (occupation, socioeconomic status, residential location, and religious belief) and school climate factors (school culture, classroom ecology, school physical plant, and school administration). Using a qualitative approach, the study interviewed six principals and six education zonal officers. The interviews were recorded, transcribed, and analyzed to identify key sub-themes and themes. The study emphasizes the crucial importance of establishing validity and reliability in qualitative research. To ensure validity, the researchers employed triangulation, member checking, peer examination, submersion, and external validation. Reliability was addressed through dependability, triangulation, audit trails, peer review, trustworthiness, and appraisal (generalization). The study recommends that schools create a more inclusive environment for all students, regardless of their background, and that parents demonstrate greater commitment to their children’s education. Furthermore, the study recommends that researchers using qualitative methods prioritize establishing validity and reliability at every stage of the research process. DOI: https://doie.org/10.0303/SER.2025971582